Lévendia, Philotimo, Kaïmos: Figures et Formes Rebelles de la Musique Grecque - Katinakis, Nathalie (Études helléniques / Hellenic Studies, 2012)
Greek music occupies a special place in the heart of the Greeks. From folk music (dimotiki) to popular music (laiki), a constellation of images and symbols are deployed in the Greek repertoire. Deeply linked to a spirit of resistance and identity preservation over the centuries, this music in its many aspects, remains one of the best gateways to understand the Hellenic imaginaire. Reviewing the main Greek musical genres, this article highlights what they reveal of history, memory and collective identity of Greece in constant renewal.